37.2k views
1 vote
How to complete the table

How to complete the table-example-1
User Rych
by
6.0k points

2 Answers

4 votes
so all you need to do is plug the x in so
7(-2)-2= -16
7(-1)-2= -9
7(0)-2= -2
7(1)-2= 5
7(2)-2= 12
User Gaellm
by
6.1k points
7 votes

Put the values of x to the equation of the function y= 7x - 2

for x= -2 → y= 7(-2) - 2 = -14 - 2 = -16

for x = -1 → y = 7(-1) - 2 = -7 - 2 = -9

for x = 0 → y = 7(0) - 2 = 0 - 2 = -2

for x = 1 → y= 7(1) - 2 = 7 - 2 = 5

for x= 2 → y= 7(2) - 2 = 14 - 2 = 12

x y

-2 -16

-1 -9

0 -2

1 5

2 12


User DhrubaJyoti
by
6.2k points